Effect of Resource Management on Diversity and Productivity of Vegetation Associated with Prosopis juliflora in Indian Arid Zone - Singh, G; Shukla, Smita (Annals of Arid Zone, 2016)
Diversity and productivity of vegetation associated with Prosopis juliflora (Swartz DC) was studied to monitor the impact of this invasive alien species on indigenous flora of the Indian desert. Resource management treatments in the form of canopy removal and trenching around tree root zone were: intact tree without trench (T1), intact tree and trench (T2), lopped tree without trench (T3), lopped tree and trench (T4) and control plots without tree (T5). Photosynthetically active radiations (PAR) reduced by 86-87% under P. juliflora. A total of 20 plant species were recorded. Species richness, diversity and evenness were significantly greater (P<0.05) in T1 and T2 as compared to T3 and T4 treatments. Treatments with intact canopy produced 2.1-fold greater biomass than the lopped ones. Decrease in relative neighbour effect (RNE) values for diversity variables and community biomass in T2 and T4 than their respective value in T1 and T3 treatments indicates positive effect of trenching. A greater difference in RNE between intact and lopped trees as compared to that between trenched and untrenched treatments showed that the beneficial effect of canopy retention was greater than trenching around tree in this environment. Temporal changes indicated highest biomass in September, thereafter it decreased by 35%, 50% and 70% in December, March and June, respectively. Conclusively, highest diversity and vegetation biomass in T2 treatment indicated beneficial effect of both canopy and trenching, which can be adopted to increase the productivity of rangelands with P. juliflora. However, optimization of density is required to increase the production of rangeland grasses. Key words: Arid region, photosynthetically active radiations, species diversity, vegetation dynamics, Indian desert, Prosopis juliflora.